Women's perceptions of strategies to address the normalisation of gambling and gambling‐related harm. (23rd June 2022) - McCarthy, Simone; Thomas, Samantha; Marko, Sarah; Pitt, Hannah; Randle, Melanie; Cowlishaw, Sean
Abstract: Objective : Research has demonstrated that gambling is becoming increasingly normalised for women. As limited research has sought to understand women's perspectives on this issue, we sought women's opinions about the factors that may contribute to the normalisation of gambling for women, and the strategies that may counter this normalisation. Methods : Semi‐structured interviews were conducted with 41 women in young and middle adulthood, aged 20‐40 years. Results : Participants suggested that gambling was normal for women because gambling environments had been designed to appeal to women, newer technologies had removed the stigma of attending physical venues, and the growing equality and independence of women. To de‐normalise gambling, women suggested addressing the influential role of marketing, designing new public education strategies, addressing the availability and accessibility of gambling, and restricting engagement with gambling products. Conclusion : This study highlighted women's perceptions of strategies to address the normalisation of gambling and the importance of providing risk information paired with broader policy reform and prevention initiatives to address the range of determinants that normalise gambling for women. Implications for public health : Involving women in advocacy and understanding their perspectives is important in developing relevant public health responses to the normalisation of gambling for women.